Characterization and application of phthalocyanine-gold nanoparticle conjugates - Tombe, Sekai Lana (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
This work presents the syntheses, photophysical and photochemical characterization of arylthio zinc phthalocyanines and their gold nanoparticle conjugates. Spectroscopic and microscopic studies confirmed the formation of the phthalocyanine-gold nanoparticle conjugates which exhibited enhanced photophysicochemical properties in comparison to the phthalocyanines. The studies showed that the presence of gold nanoparticles significantly lowered fluorescence quantum yields and lifetimes. However, this interaction did not restrict the formation of excited singlet and triplet states and hence the formation of singlet oxygen required for photocatalysis. The conjugates showed significantly higher singlet oxygen quantum yields and therefore enhanced photocatalytic activity compared to the phthalocyanines. The zinc phthalocyanines and their gold nanoparticle conjugates were successfully incorporated into electrospun polymer fibers. Spectral characteristics of the functionalized electrospun fibers indicated that the phthalocyanines and phthalocyanine-gold nanoparticle conjugates were bound and their integrity was maintained within the polymeric fiber matrices. The photophysical and photochemical properties of the complexes were equally maintained within the electrospun fibers. The functionalized fibers were applied for the photoconversion of 4-chlorophenol and Orange G as model organic pollutants.,Microsoftï¿½ Word 2010,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Phthalocyanines; Gold; Zinc; Nanoparticles; Bioconjugates; Photochemistry; Photocatalysis; Electrospinning; Polymers; Pollutants; Phenols; Azo dyes